2022
DOI: 10.1080/19768354.2022.2104925
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin reduces fear, anxiety, and depression in rats with post-traumatic stress disorder

Abstract: Exposure to severe stress can lead to the development of neuropsychiatric disorders, including post-traumatic stress disorder (PTSD). The cause of PTSD is dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis and an imbalance of monoamines. Fruits and vegetables contain large amounts of luteolin (LU; 3′,4′,5,7-tetrahydroxylflavone), which has various pharmacological activities such as anti-inflammatory, antioxidant, and anti-allergic effects. We investigated the effects of LU on fear, depression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“… 44 Luteolin can also lead to an increase in norepinephrine and decreased serotonin levels in the medial prefrontal cortex and hippocampus, showing antidepressant and anxiolytic effects. 45 In this study, the main active constituents of QUF3 included quercetin, luteolin, sophoranol, kaempferol, and neurotoxin inhibitors, which is consistent with the results of some previous studies.…”
Section: Discussionsupporting
confidence: 92%
“… 44 Luteolin can also lead to an increase in norepinephrine and decreased serotonin levels in the medial prefrontal cortex and hippocampus, showing antidepressant and anxiolytic effects. 45 In this study, the main active constituents of QUF3 included quercetin, luteolin, sophoranol, kaempferol, and neurotoxin inhibitors, which is consistent with the results of some previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Kaempferol increases the AKT/β-linked protein cascade in the prefrontal cortex and reduces in ammatory factor levels (Gao, Wang et al 2019, Silva Dos Santos, Gonçalves Cirino et al 2020). Lignocaine reduces IL-6 production by astrocytes, decreases serum levels of IL-6, TNF-α and corticosterone, and increases mature brain-derived neurotrophic factor (BDNF), dopamine and norepinephrine levels to exert antidepressant effects (Achour, Ferdousi et al 2021, Sur andLee 2022). Furthermore, and most notably, the normal neutrophil group was signi cantly higher than the MDD group, defying the norm of the immunoin ammatory doctrine.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 LUT also improves a variety of depression-like behaviors through different pathways. [15][16][17] Our previous studies have suggested that LUT can enhance the brain's transport of folic acid to promote hippocampal neurogenesis and alter the axonal guidance pathway in cerebrospinal fluid to exert its therapeutic effect on LOD. 5,18 Metabolomics technology is considered a valuable tool in the study of central nervous system diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LUT has cognitive effects in animal models of cognitive deficits induced by high‐fat diets or aging, mainly related to its pharmacological anti‐inflammatory properties 13,14 . LUT also improves a variety of depression‐like behaviors through different pathways 15–17 . Our previous studies have suggested that LUT can enhance the brain's transport of folic acid to promote hippocampal neurogenesis and alter the axonal guidance pathway in cerebrospinal fluid to exert its therapeutic effect on LOD 5,18 …”
Section: Introductionmentioning
confidence: 99%